Calf Thymus Polypeptide Restrains the Growth of Colorectal Tumor via Regulating the Intestinal Microbiota-Mediated Immune Function - Li, Lanzhou; Zhao, Chenfei; Kong, Fange; Li, Yi-Cong; Wang, Chunxia; Chen, Shanshan; Tan, Hor-Yue; Liu, Yang; Wang, Di (Frontiers in Pharmacology, 2022)
Calf thymus polypeptide (CTP), with a molecular mass of less than 10 kilodalton, is prepared from the thymus of less than 30-day-old newborn cattle. In the present study, the inhibitory function of CTP in colorectal cancer (CRC) was investigated in B6/JGpt-Apcem1Cin(MinC)/Gpt (ApcMin/+) mice. CTP hampered tumor development and enhanced the ratio of CD3e-NK1.1+ cells by 113.0% and CD3e+CD28+ cells by 84.7% in the peripheral blood of ApcMin/+ mice. CTP improved the richness, diversity and evenness of the intestinal microbiota of ApcMin/+ mice, particularly by regulating the abundance of immune-related microorganisms. CTP effectively regulated the expression of immune-related cytokines, such as interleukin (IL)-2 (15.19% increment), IL-12 (17.47% increment), and transforming growth factor (TGF)-β (11.19% reduction). Additionally, it enhanced the levels of CD4 and CD8, as well as the ratio of helper T lymphocytes (Th)1/Th2 in the spleen and tumors of ApcMin/+ mice. In CTP-treated mice, reduced levels of programmed death-1 (PD-1), programmed cell death-ligand 1 (PD-L1), cytotoxic T lymphocyte associated antigen 4 (CTLA4), and activated nuclear factor of activated T cells 1 (NFAT1) and nuclear factor κB (NF-κB) p65 signaling were noted. Collectively, the anti-CRC effect of CTP is related to the modulation of intestinal microbiota-mediated immune function, which provides a reference for CTP as a therapeutic drug or a combination drug used in CRC treatment in the clinical setting.